Synthesis of naphthalimide-carborane and metallacarborane conjugates: Anticancer activity, DNA binding ability - Nekvinda, Jan; Różycka, Daria; Rykowski, Sebastian; Wyszko, Eliza; Fedoruk-Wyszomirska, Agnieszka; Gurda, Dorota; Orlicka-Płocka, Marta; Giel-Pietraszuk, Małgorzata; Kiliszek, Agnieszka; Rypniewski, Wojciech; Bachorz, Rafał; Wojcieszak, Jakub; et al. (Bioorganic chemistry, 2020)
The development of 1,8-naphthalimide derivatives as DNA-targeting anticancer agents is a rapidly growing area and has resulted in several derivatives entering into clinical trials. One of original recent developments is the use of boron clusters: carboranes and metallacarboranes in the design of pharmacologically active molecules. In this direction several naphthalimide-carborane and metallacarborane conjugates were synthesized in the present study. Their effect on a cancer cell line - cytotoxicity, type of cell death, cell cycle, and ROS production were investigated. The tested conjugates revealed different activities than the leading members of the naphthalimides family, namely mitonafide and pinafide. These derivatives could induce G0/G1 arrest and promote mainly apoptosis in HepG2 cell line. Our investigations demonstrated that the most promising molecule is N-{[2-(3,3'-commo-bis(1,2-dicarba-3-cobalta(III)-closo-dodecaborate-1-yl)ethyl]-1'-aminoethyl)}-1,8-naphthalimide] (17). It was shown that 17 exhibited cytotoxicity against HepG2 cells, activated cell apoptosis, and caused cell cycle arrest in HepG2 cells. Further investigations in HepG2 cells revealed that compound 17 can also induce ROS generation, particularly mitochondrial ROS (mtROS), which was also proved by increased 8-oxo-dG level in DNA. Additionally to biological assays the interaction of the new compounds with ct-DNA was studied by CD spectra and melting temperature, thus demonstrating that these compounds were rather weak classical DNA intercalators.
Keywords: Metallacarborane; oxidační stres; Cell Line; vazebná místa; protinádorové látky; Cell Proliferation; Structure-Activity Relationship; buňky Hep G2; Drug Screening Assays, Antitumor; molekulární struktura; Molecular Structure; Naphthalimides; DNA nádorová; vztah mezi dávkou a účinkem léčiva; Boranes; naftalimidy; Organometallic Compounds; vztahy mezi strukturou a aktivitou; DNA, Neoplasm; Binding Sites; lidé; Humans; borany; Hep G2 Cells; Carborane; buněčné linie; proliferace buněk; screeningové testy protinádorových léčiv; Anticancer activity; Oxidative Stress; Dose-Response Relationship, Drug; Antineoplastic Agents; organokovové sloučeniny